Evaluation of the Speed and Aerobic Capacity of Elite Greek Soccer Referees in A΄ and B΄ National Division - Trikalis Χρήστος; Papanikolaou Ζήσης; Soulas Δημήτριος; Gerodimos Βασίλειος (Inquiries in Physical Education and Sport, 2007)
The aim of this study was to assess selected capacities of physical condition in elite Greek soccer referees officiating in A and B National division for the Greek National Championships. The possible changes of speed performance and aerobic capacity within a year and differences between the referees officiating in the A and B division were assessed. Sixty one (61) elite Greek soccer referees officiating in A΄ (n=20) and B΄ division (n=41) for the National Greek Championship in 2005-2006 were assessed. Speed performance was assessed through 50m and 200m run tests and the aerobic capacity was evaluated utilizing the Cooper test. There was a two-minutes break between the speed tests and at least 8 minutes break before the Cooper test. A Two Way ANOVA with repeated measures (time of year x division) was used to analyze the results. The results showed that there were no differences between the performance levels of the A and B division referees regarding the Cooper test, the 50m and 200m run tests as well as between the measurements within the year. These results indicate that Greek soccer referees can maintain adequate fitness throughout the year. Although A΄ division referees are older than B΄ division referees (Α΄ 35.5 ± 3.5 y, Β΄ 32.7 ± 3.1 y), they train for a longer period of time than those of B΄ division (Α΄: 4.3 ± .8, Β ΄: 3.8 ± 1.2, weekly training sessions). Both A΄ and B΄ division referees officiate in approximately the same matches and, as they are considered almost professional referees, it seems that they place great importance on their training. In addition, based on FIFA standards, Greek referees are considered to be in a high level of aerobic capacity and speed, physical condition factors which are regarded to be important for their performance as referees.